Genealogical Cartography of the “Narratives of Discomfort”: Chile During the Transition Between 1990-1998 [Cartografía Genealógica de Las “Narrativas del Malestar”: El Chile de la Transición Entre 1990-1998] - Moyano-Barahona, C (Universidad de Concepcion, 2021)
This article approaches, from an intellectual history point of view, the set of critical narratives of the Chilean transition during the 1990s. By exploring various texts, supports, debates, and authors, it shapes a genealogical cartography of the first set of criticisms that circulated in the public space and that were the support of an imaginary that will collaborate with the erosion of the historical time’s story of the “transition and democratic consolidation”, installed by the intellectual elite of the Concertation of Parties for Democracy. © 2021, Universidad de Concepcion. All rights reserved.